2016
DOI: 10.1007/s11274-016-2057-9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and antioxidant activity of a novel collagen from Pelodiscus sinensis

Abstract: Collagen is the main structural protein of various connective tissues in animals and naturally plays an important role within the body. It is increasingly used within certain areas, such as medicine, citology and cosmetology. The soft-shelled turtle (Pelodiscus sinensis) is a commercially important aquatic species rich in collagen. In this study, a novel collagen gene fragment of 756 bp, which encodes 252 deduced amino acid residues, including 25 conserved Gly-X-Y motifs, was cloned from a soft-shelled turtle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The DPPH radical scavenging activity of fluorescent phycocyanin was tested according to the method of Xu et al [ 32 ], with some modifications. The purified recombinant protein was diluted with KPB to 50, 100, 150, 200, and 250 µg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The DPPH radical scavenging activity of fluorescent phycocyanin was tested according to the method of Xu et al [ 32 ], with some modifications. The purified recombinant protein was diluted with KPB to 50, 100, 150, 200, and 250 µg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The soft-shelled-turtle (Pelodiscus sinensis) is a commercially important aquatic species rich in collagen. Investigations conducted by the researchers Xu et al (2016), demonstrated the antioxidant activity with the elimination of free radicals in approximately 98.9% from a new collagen extracted from P. sinensis. More recent studies have also demonstrated that antioxidant enzymes, peroxiredoxins, isolated softshelled-turtle have been shown to influence the defense against oxidative and modular stress in the immunohistochemical response in vitro (Zhang et al, 2019).…”
Section: Determination Of Lbfpe's Antioxidant Activitymentioning
confidence: 98%
“…A total of 400 µM Isopropyl-β-D-thiogalactopyranoside (IPTG) was added to the medium to induce expression, which was maintained at 20 • C. Bacteria were collected by centrifugation and ultrasonically crushed to obtain a crude extract. The His-tagged proteins were subsequently isolated using a His GraviTrap column (Cytiva, Marlborough, MA, USA) and concentrated using an ultrafiltration filter (Millipore, St. Louis, MO, USA) to obtain the target proteins [46]. The detection of biolayer interferometry was performed as previously described [47,48].…”
Section: Expression and Purification Of Rta And Its Mutantsmentioning
confidence: 99%